Islamic Economic Law and Asset Redistribution: A Study of Distributive Justice in Parepare City - Anggeryani Syam; Zainal Said; Hannani Yunus (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2026)
Economic inequality remains a persistent structural challenge in developing societies, particularly in the unequal ownership and control of productive assets, a condition that continues to shape the socio-economic landscape of Parepare City. This study aims to analyze the contribution of the concept of distributive justice in Islamic Economic Law to mitigating asset distribution inequality in the community of Parepare City. The research employed a descriptive qualitative method with a phenomenological approach. Primary data were collected through in-depth interviews with Islamic economics scholars, administrators of zakat and waqf institutions, and micro- and small-scale business owners in Parepare City. Secondary data were obtained from reports on poverty statistics, income distribution, and national zakat management. The findings reveal that asset distribution inequality in Parepare City is largely driven by structural barriers within market mechanisms that lead to the concentration of capital among certain economic groups. As a result, low-income communities experience limited access to productive economic resources. The concept of distributive justice in Islamic Economic Law has strong relevance as an instrument for mitigating asset inequality. Its implementation can be realized through the transformation of zakat and waqf management from a charitable-oriented approach into a productive economic empowerment model. Furthermore, the synchronization of more inclusive local regulations is necessary to ensure equitable access to economic resources and to strengthen the economic empowerment of lower-income communities.